Legal Compliance and Regulatory Challenges Towards The Use of AI Algorithms in Facial Recognition Systems in Public Secrets - Sutrisno, Anom (Indonesian Cyber Law Review, 2025)
This study examines legal compliance and regulatory challenges in the use of AI algorithms for facial recognition systems in the public sector, with a comparative analysis between Indonesia and neighboring countries such as Singapore, Malaysia, and Thailand. The study uses a qualitative comparative approach based on legal documentation and regulatory analysis to explore the extent to which public institutions comply with applicable laws and regulations, identify regulatory gaps, and assess accountability and transparency mechanisms. The findings indicate that Indonesia exhibits moderate legal compliance due to limited technical guidelines, inconsistent internal monitoring, and underdeveloped audit procedures, while Singapore and Malaysia demonstrate higher levels of compliance supported by adaptive regulations, systematic audits, and comprehensive technical procedures. Regulatory challenges in Indonesia include slow adaptation of laws to rapidly evolving AI technologies, inadequate oversight, and unclear operational procedures, which can increase the risk of data misuse and undermine public trust. The study concludes that strengthening technical guidelines, conducting regular audits, increasing transparency, and adopting best practices from neighboring countries are important steps to improve legal compliance and effective AI regulation in the Indonesian public sector. This research contributes to policymaking and academic understanding of AI governance in public institutions.